Student Nurses' Perception of Good Death and Religious Coping Styles - Aktura, Seher Cevik; Saritas, Seyhan Citlik; Karakas, Nese (Sage Publications Inc, 2025)
This research aims to examine the perception of the good death and religious coping styles of student nurses. The research is a correlational descriptive study. The research was conducted with 358 nursing students at a state university in the east of Turkey. It was found in the study that students had a good perception of death (58.83 +/- 6.12) and mostly used positive religious coping styles (positive/24.55 +/- 3.71, negative/13.31 +/- 4.21). As a result of the correlation analysis, a weakly significant positive relationship was determined between good death perception and positive religious coping (p < .001).This study observed that students' perceptions of good death increased along with their positive religious coping styles.
Keywords: nursing student; good death; religious coping styles